1991
DOI: 10.1071/sr9910425
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the physical properties of a vertisol following an irrigation of cotton as influenced by the previous crop

Abstract: Structural degradation of Vertisols depresses cotton lint yield by extending the period of waterlogging following irrigation or heavy rainfall. Break crops such as wheat and safflower are often grown without irrigation to improve the macroporosity of degraded Vertisols, by encouraging deep cracking, after several years of cotton production.Investigations were made into the effects of cultivated fallow, wheat and safflower on soil structure, and the growth of a subsequent cotton crop. The tests reported in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This has been used as evidence for a lack of deep drainage. However, Chan and Hodgson (1981) also show full soil water profiles 3 weeks after a pre-irrigation and following a winter fallow, and Hulme et al (1991) show a reasonably full profile after a cultivated fallow. This indicates that deep infiltration and drainage are possible, but that the method or rate of wetting is important in determining the outcome.…”
Section: Final Infiltration Rates For Soils Used For Irrigationmentioning
confidence: 95%
See 1 more Smart Citation
“…This has been used as evidence for a lack of deep drainage. However, Chan and Hodgson (1981) also show full soil water profiles 3 weeks after a pre-irrigation and following a winter fallow, and Hulme et al (1991) show a reasonably full profile after a cultivated fallow. This indicates that deep infiltration and drainage are possible, but that the method or rate of wetting is important in determining the outcome.…”
Section: Final Infiltration Rates For Soils Used For Irrigationmentioning
confidence: 95%
“…Both Chan and Hodgson (1981) in the Namoi Valley and Hulme et al (1991) in the Macquarie Valley found that furrow irrigation water did not infiltrate into sodic soils beyond 0.8 m, even in soil at permanent wilting point to a depth of 1.5 m before irrigation. This has been used as evidence for a lack of deep drainage.…”
Section: Final Infiltration Rates For Soils Used For Irrigationmentioning
confidence: 97%
“…For adequate gaseous exchange between the soil profile and the atmosphere, a minimum AFP value of 0.10 cm 3 cm À3 is generally required (McGarry, 1993). However, Hulme et al (1991) suggested that critical AFP values for plant production on swelling clays may be substantially different or indeed lower than 0.10 cm 3 cm À3 . Critical AFP values for vertosols in the order of 0.05 cm 3 cm À3 quoted by Gardner (1988) appeared to be the case at this site.…”
Section: Bulk Densitymentioning
confidence: 97%
“…Ekinci et al (1993) stated that Vertisol soils of Karacakilavuz in Tekirdag Province owned poor physical and management properties, due to high amounts (53-56%) of smectite clay mineral in their texture. Statements related to unfavourable (heavy) texture of the studied soils are reported also in the foreign scientific literature (Hulme et al 1991, McKenzie et al 1994, Islam et al 1994). Zurovec and Cadro (2016) also determined that water amounts in the soil profile vary from soil to soil, and the highest amount of water in the soil over the entire water potential range (pF), is available in Luvisol, and the lowest in Fluvisol soil profiles.…”
Section: Resultsmentioning
confidence: 93%